INTELLIGENT COMPUTER NETWORK FOR RAILWAY TRANSPORT USING NEURAL NETWORK FOR DETERMINING THE OPTIMAL ROUTE - Пахомова, Вікторія; Будніков, Олександр (Modern engineering and innovative technologies, 2025)
At the present stage, the information and telecommunications system of railway transport uses local area networks of Ethernet family technologies and the OSPF protocol, when used in real time, a problem arises due to constant changes in the volume of tran